2019
DOI: 10.1111/jfpp.13952
|View full text |Cite
|
Sign up to set email alerts
|

Microwave processing impact on physicochemical and bioactive attributes of optimized peach functional beverage

Abstract: The health benefits of blended functional drinks make them popular among consumers and a highly profitable product sector. In this study, the compositions of peach juice, plum juice, and sugar solution were optimized by D‐optimal mixture design in the ratio of 72:25:3 to develop a functional beverage with acceptable sensory attributes. The results also showed that a blending of fruit juices significantly increases the amount of bioactive compounds (TPC: 432 µg/100 ml; TFC: 169.5 µg CE/100 ml) along with antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Our findings are in agreement with that of Valadez-Carmona et al (2017) who reported that MC drying of cocoa pod husk enhanced its antioxidant properties and reduced its enzyme (PPO) activity. MC drying has also been reported to improve the extraction efficiency of bioactive compounds of most dehydrated products (An et al, 2016a;Sattar et al, 2019). The highest loss of antioxidant activity that was observed in the PVD ginger samples may be due to the damage of the cell wall which then activated the release of hydrolytic and oxidative enzymes.…”
Section: Effects Of Different Drying Methods On the Antioxidant Activities Of Gingermentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in agreement with that of Valadez-Carmona et al (2017) who reported that MC drying of cocoa pod husk enhanced its antioxidant properties and reduced its enzyme (PPO) activity. MC drying has also been reported to improve the extraction efficiency of bioactive compounds of most dehydrated products (An et al, 2016a;Sattar et al, 2019). The highest loss of antioxidant activity that was observed in the PVD ginger samples may be due to the damage of the cell wall which then activated the release of hydrolytic and oxidative enzymes.…”
Section: Effects Of Different Drying Methods On the Antioxidant Activities Of Gingermentioning
confidence: 99%
“…The ginger slices (0.3 kg) were dried at a temperature of 60°C, 50 Hz frequency, and 850 W power Sattar et al (2019) Pulsed vacuum drying (PVD)…”
Section: Drying Techniques Conditions Referencesmentioning
confidence: 99%
“…The MD was conducted by following the method previously reported by Sattar et al () with little adjustment. The ginger slices (0.9 kg) were dried in a microwave oven (model NJO7‐3, Jiequan Apparatus co. Ltd Nanjing, China) at a temperature of 60°C, 50 Hz frequency, and 850 W power.…”
Section: Methodsmentioning
confidence: 99%
“…In several juices, the applications of the MDs were in functional fruit juices [24,[67][68][69][70][71][72][74][75][76], powders [66,73], and the quality of sugarcane [77] juice. In addition, the MDs have often been applied in formulations of probiotic and energetic functional juices to improve these products' sensory, antioxidant, and nutritional properties with potential benefits for consumers' health [66,68,72,73].…”
Section: Application Of Mixture Design In Beveragementioning
confidence: 99%
“…In addition, the MDs have often been applied in formulations of probiotic and energetic functional juices to improve these products' sensory, antioxidant, and nutritional properties with potential benefits for consumers' health [66,68,72,73]. Among the most common uses of MDs in several juices, there were reports of studies that evaluated the reduction in calories in juices [67], the addition of stevia [74], and the inclusion of phenolic and bioactive compounds in juices [71]. Part of these studies focuses on investigating Brazilian native fruits, such as acerola [67], and other fruits native to the Brazilian Cerrado, such as Marolo, Mangaba, and Cagaita [75].…”
Section: Application Of Mixture Design In Beveragementioning
confidence: 99%